Molecular and Cellular Effects of In Vitro Shockwave Treatment on Lymphatic Endothelial Cells - Rohringer, Sabrina; Holnthoner, Wolfgang; Hackl, Matthias; Weihs, Anna M.; Rünzler, Dominik; Skalicky, Susanna; Karbiener, Michael; Scheideler, Marcel; Pröll, Johannes; Gabriel, Christian; Schweighofer, Bernhard; Gröger, Marion; et al. (PLOS ONE, 2014)
Extracorporeal shockwave treatment was shown to improve orthopaedic diseases and wound healing and to stimulate lymphangiogenesis in vivo. The aim of this study was to investigate in vitro shockwave treatment (IVSWT) effects on lymphatic endothelial cell (LEC) behavior and lymphangiogenesis. We analyzed migration, proliferation, vascular tube forming capability and marker expression changes of LECs after IVSWT compared with HUVECs. Finally, transcriptome- and miRNA analyses were conducted to gain deeper insight into the IVSWT-induced molecular mechanisms in LECs. The results indicate that IVSWT-mediated proliferation changes of LECs are highly energy flux density-dependent and LEC 2D as well as 3D migration was enhanced through IVSWT. IVSWT suppressed HUVEC 3D migration but enhanced vasculogenesis. Furthermore, we identified podoplaninhigh and podoplaninlow cell subpopulations, whose ratios changed upon IVSWT treatment. Transcriptome- and miRNA analyses on these populations showed differences in genes specific for signaling and vascular tissue. Our findings help to understand the cellular and molecular mechanisms underlying shockwave-induced lymphangiogenesis in vivo.